Characterization and Modeling of CdS/CdTe Heterojunction Thin-Film Solar Cell for High Efficiency Performance - Hamid Fardi; Fatima Buny (International Journal of Photoenergy)
Device simulation is used to investigate the current-voltage efficiency performance in CdTe/CdS photovoltaic solar cell. The role of several limiting factors such as back contact Schottky barrier and its relationship to the doping density and layer thickness is examined. The role of surface recombination velocity at back contact interface and extended CdTe layer is included. The base CdS/CdTe experimental device used in this study shows an efficiency of 16-17%. Simulation analysis is used to optimize the experimental base device under AM1.5 solar spectrum. Results obtained indicate that higher performance efficiency may be achieved by adding and optimizing an extended CdTe electron reflector layer at the back Schottky contact. In the optimization of the CdS/CdTe cell an extended electron reflector region with a barrier height of 0.1 eV and a doping density of  cm−3 with an optimum thickness of 100 nm results in best cell efficiency performance of 19.83% compared with the experimental data.